Cost-Effective and Scalable Synthesis of 4-Bromo-1,2-dimethyl-1H-imidazole: A Key Building Block for Bioactive Molecules - Vetrichelvan, Muthalagu; Lanke, Veeranjaneyulu; Chandu, Bellam; Mathur, Arvind; Gupta, Anuradha (SynOpen, 2023)
A cost-effective, scalable, high-yielding, and commercially viable synthesis of 4-bromo-1,2-dimethyl-1H-imidazole (1), an important building block to construct various bioactive molecules has been established. The main feature of this method includes the selection of appropriate starting material 1,2-dimethyl-1H-imidazole in which the existing issue of regioisomer formation is circumvented and the selective debromination is accomplished by using isopropyl magnesium chloride.
Keywords: bromination; debromination; imidazole derivative; cost-effective; scalable